Pemanfaatan Antibodi Monoklonal dalam Immunoassay untuk Deteksi Baculovirus oryctes - Susamto Somowiyarjo; Hery Haryanto; Sri Wening (Universitas Gadjah Mada, 2000)
The application of non-precoated Indirect Enzyme-Linked Immunosorbent Assay (ELISA) and Dot Immunobinding Assay (DIBA) employing monoclonal antibodies (MCA) against Yogyakarta isolate of Baculovirus oryctes Huger. was described. The MCA-Bv-4 having subclass of IgG2a and titer in vitro of 10^4 - 10^5 proved to be useful antibody for virus detection. The great potential of I-ELISA using MCA-Bv-4 has been it's specificity being able to discriminate between healthy an virus-infected coconut beetle (Oryctes rhinoceros L.). The assay could also differentiate between B. oryctes and Monodon baculovirus, the pathogen of shrimp disease. The best tissue for preparing virus antigen from crude extract was found to be the midgut of the beetle. Head, thorax, abdomen and tibia were not suitable for preparing the test antigen. The crude extract of beetle showed high endogenous enzyme activity to the substrate of DIBA, which precluded the detection of B. oryctes using DIBA. The MCA-Bv-4 could be used to improve the monitoring of the virus to support the program of biological control of coconut beetle using B. oryctes.